1984
DOI: 10.17741/bgsf/56.1-2.009
|View full text |Cite
|
Sign up to set email alerts
|

Origin and geodynamic evolution of the Archean crust of eastern Finland

Abstract: The Archaean crust of eastern Finland is composed of three main lithological units: -Gneissic basement. It was originally composed of tonalites, trondhjemites and granodiorites emplaced at 2.86 G.a. and 2.62 G.a. and subsequently transformed into grey gneisses. The parental magmas originated from the mantle in a two-stage process: (i) formation of a basaltic crust, (ii) melting of this crust transformed into garnet-bearing amphibolite. Field, petrological and geochemical data argue in favour of a subduction-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The geodynamic models for the Kuhmo Greenstone Belt included subduction-related magmatic arc or marginal basin settings (Piirainen, 1988;Taipale, 1983Taipale, , 1988 or crustal downsagging (Martin et al, 1984). Luukkonen (1992) proposed intracontinental rift model, in which he explained the origin and evolution of the belt by the mantle plume arising from a thermal boundary layer deep within mantle, or from the core-mantle boundary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The geodynamic models for the Kuhmo Greenstone Belt included subduction-related magmatic arc or marginal basin settings (Piirainen, 1988;Taipale, 1983Taipale, , 1988 or crustal downsagging (Martin et al, 1984). Luukkonen (1992) proposed intracontinental rift model, in which he explained the origin and evolution of the belt by the mantle plume arising from a thermal boundary layer deep within mantle, or from the core-mantle boundary.…”
Section: Discussionmentioning
confidence: 99%
“…The main theories include subduction-related magmatic arc or marginal basin settings (Piirainen, 1988;Taipale, 1983Taipale, , 1988, crustal downsagging (Martin et al, 1984) and intracontinental rift model (Luukkonen, 1992).…”
Section: Regional Geologymentioning
confidence: 99%
“…The temperature and plasticity increase at the deep crustal level results in diapiric ascent of plutonic rocks and in downward motion of the supracrustal formations (sagduction; Gorman et al, 1978). Consequently, most plutonites are located in domes while greenstone belts appear in basin domains as described in the Archean of the Dharwar craton in south India (Choukroune et al, 1995;Bouhallier et al, 1995;Chardon et al, 1998) or in the Baltic Shield (Martin et al, 1985;Martin, 1987). Similar structures appear in the Jequié granulitic block of the São Francisco craton (Bahia State NE Brazil) (Barbosa, 1990; Barbosa and Sabaté, 2002;Fornari and Barbosa, 1994).…”
Section: Introductionmentioning
confidence: 90%
“…The Kuhmo-Suomussalmi-Tipasjärvi belt (referred to here as the Kuhmo greenstone belt; Fig. 2) has been variably attributed to intracontinental rifting (Martin et al, 1984;Luukkonen 1992Luukkonen , 2001, aborted rifting preceded and followed by subduction (Piirainen, 1988), island arc magmatism (Taipale 1983(Taipale , 1988, and back-arc rifting (Gaál & Gorbatschev, 1987). In addition, Kontinen et al (2007) have suggested that the Nurmes paragneisses (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In the Kuhmo district, the migmatitic TTG gneisses or associated banded amphibolites have been considered as the oldest rocks in the area (cf. Martin et al, 1984;�uukkonen, 1992). Previously reported age determinations from the migmatites are based on conventional multigrain U-Pb analyses (�uukkonen, 1985) and wholerock Rb-Sr method (e.g.…”
Section: Introductionmentioning
confidence: 99%